K2S2O8-Activated Friedel–Crafts Type Alkylation of Indoles with α-Amido Sulfones - Wu, Xiaoyan; Xue, Lu; Luo, Shilong; Jia, Shiqi; Ao, Jun; Qin, Wenling (Synthesis, 2017)
A K2S2O8-activated regioselective alkylation of α-amido sulfones at the C-3 position of indoles is reported. The protocol developed herein provides an alternative new strategy to the previous approach by using Lewis acid, clay, and resin as catalyst for this Friedel–Crafts type alkylation of indoles with α-amido sulfones. The formed product bears a versatile transformable sulfone group and an amino group. The reaction condition is tolerant to a wide range of substrates, including a series of indoles with electron-withdrawing and electron-donating groups at different positions. Moreover, a variety of α-substituted phenylamido sulfones and some α-aliphatic amido sulfones also give the desired products in modest yield. Furthermore, a preliminary mechanism study was performed and the plausible reaction mechanism is discussed.
Keywords: K2S2O8; indole alkylation; α-amido sulfone; Friedel–Crafts reaction